Breastfeeding and HIV: the challenge of a potential paradigm shift (Actualizaciones en Sida e Infectología, 2024)
For more than four decades, sufficient scientific evidence has been generated to understand the mechanisms involved in vertical transmission (VT) of HIV, which has allowed the design of interventions that, to date, have made substantial progress in preventing new cases. These evidence-based interventions cover both gestation and delivery as well as the care of those exposed perinatally (1).In addition, there are some paradigms associated with HIV-VT that have guided all related programming recommendations and actions. Viral load suppression of the gestational person as the most important variable in preventing transmission during pregnancy and delivery, coupled with the replacement of human breastfeeding with formula milk, are certainly two such paradigms in high- and middle-income countries.Simultaneously, there has also been growing evidence of the benefits of human breastfeeding for both the health of the breastfeeder and the health of the infants. On the other hand, an analysis of the exclusive breastfeeding process describes common practices of incorporating formula milk before the age of six months in countries where access to formula milk is facilitated.In recent years, new evidence from settings where breastfeeding substitution in people living with HIV was not possible or recommended has shown that antiretroviral drug (ARV) use in breastfeeding people with HIV significantly reduces the risk of postnatal transmission. In people who have sustained viral suppression and who exclusively breastfeed for a period of six months, the risk of transmission may be less than 1% (2, 3).Studies in high-income countries have confirmed this estimate of low risk associated with breastfeeding in the context of ARV therapy (4) and have led to the relaxation of the strict substitution of breastfeeding by the recommendation to inform about neonatal feeding alternatives in the setting of sustained viral suppression within a shared decision-making process (5). It is important to remember that human breastfeeding transmission has been documented despite sustained viral suppression. While the mechanism has not yet been demonstrated, it is known that in addition to cell-free HIV RNA, human milk contains immune cells that may harbour HIV-DNA proviruses that could be capable of infecting the infant.The arrival of scientific evidence, leading to the revision of a prevention paradigm established for decades, poses an enormous challenge for health teams. Knowledge transfer tools are particularly important in this situation. It is necessary to connect and relate new scientific evidence with actions aimed at incorporating and guiding the use of this new health-related practice. It is a priority to carry out a comprehensive process that includes: assessment of the importance of the problem, analysis of the available evidence, and adaptation to the legal/regulatory, cultural and service access context. Potential barriers must then be identified, implementation interventions designed and impact evaluated.In Argentina, vertical transmission of HIV continues to be a public health problem. While significant progress has been made, the proposed elimination targets have not yet been met. Barriers identified include: gestational persons without virological suppression or without adequate virological testing during pregnancy, delayed HIV diagnosis of perinatally-exposed infants, and loss to follow-up. Various forms of stigma and violence associated with adverse biomedical outcomes in women with HIV have also been described. On the other hand, problems persist in the reporting of surveillance events in gestational and exposed persons that make it difficult to obtain information for programmatic decision-making.It is important to highlight that the legal and regulatory framework related to vertical transmission of HIV in Argentina is robust and explicit in determining that the practice of breastfeeding in the context of HIV should not be criminalized or generate any discrimination. As an example among several laws in force, National Law 27,675 on Comprehensive Response to HIV, Viral Hepatitis, other Sexually Transmitted Infections and Tuberculosis establishes the “right to receive comprehensive assistance and dignified and respectful treatment, without discrimination or criminalization of any kind, in all areas due to their health condition.” Its Article 11 establishes “the right of every pregnant woman and/or person with gestational capacity living with HIV to be provided with the necessary information related to their health and that of their child, both during pregnancy and postpartum. Such information shall be up-to-date, clear and evidence-based.” Receiving information on the different forms of neonatal feeding available to women with HIV is a right to information that must be guaranteed.In this scenario, since 2023, an intersectoral process was initiated to analyze the situation of breastfeeding and HIV in Argentina. As part of this process, the Argentine Society of Infectious Diseases generated the first recommendations on breastfeeding and HIV in the context of ARV use. The recommendation against breastfeeding is maintained for people living with HIV, but a series of actions are detailed so that health teams can accompany those people with sustained viral suppression and who, after receiving complete information, decide to breastfeed (6). Those recommendations describe the possible scenarios, the therapeutic indications of ARVs in the context of breastfeeding and the possible clinical events for which breastfeeding should be suspended.Effective breastfeeding is an individual and complex process, in which cultural, emotional and family dimensions are particularly relevant. In the case of people living with HIV, there is also the need to maintain adequate adherence to ARV treatment, where difficulties have been described during the postpartum period. The team that accompanies this process must be solidly trained and made up of all the specialties that the individual assessment of each situation requires. Linking with networks of people living with HIV especially dedicated to breastfeeding can add shared experiences and support.  The actual access to both adult and pediatric healthcare services in each particular situation is another dimension to be taken into account during the decision-making process.The challenge remains to generate scientific evidence on this issue in real-life scenarios that will allow us to know if we are indeed facing a paradigm shift in the prevention of vertical transmission of HIV.
Keywords: HIV; breastfeeding; vertical transmission